Interpretation of sexual secondary characteristics (SSCs) in regulatory testing for endocrine activity in fish - Wheeler, James R.; Segner, Helmut; Weltje, Lennart; Hutchinson, Thomas H. (Chemosphere (Oxford), 2020)
Secondary sexual characteristics (SSCs) are important features that have evolved in many fish species because of inter-individual competition for mates. SSCs are crucial not only for sexual selection, but also for other components of the reproductive process and parental care. Externally, they are especially clear in males (for instance, tubercles, fatpad, anal finnage, colouration) but are also externally present in the females (for instance, ovipositor). These characters are under hormonal control and as such there has been much interest in incorporating them as measures in fish test methods to assess the potential endocrine activity of chemicals. Here we describe the external SSCs in typical laboratory test species for endocrine testing - fathead minnow (Pimephales promelas), Japanese medaka (Oryzias latipes), zebrafish (Danio rerio) and the three-spined stickleback (Gasterosteus aculeatus L.). We also provide some examples and discuss the utility of SSC responses to the endocrine activity of chemicals in the field and the laboratory. This paper is not aimed to provide a comprehensive review of SSCs in fish but presents a view on the assessment of SSCs in regulatory testing. Due to the current regulatory importance of establishing an endocrine mode-of-action for chemicals, we also consider other, non-endocrine factors that may lead to SSC responses in fish. We conclude with recommendations for how the assessment of SSCs in fish could be usefully incorporated into the endocrine hazard and risk assessment of chemicals.